BOOK REVIEW OF ANIMAL INSTINCTS WRITTEN BY NELL DIXON - Nurwanti, Endah (LANTERN (Journal on English Language, Culture and Literature), 2014)
This book review describes the struggle of animal sanctuary owner, Clodagh, to maintain her sanctuary under the theme of love. The purpose of this book review is to discuss Clodagh as the main character along with the plot and the theme she sets in. Describing intrinsic elements of the novel, the writer discusses the plot and the theme in relation to the main character. From this review, the writer finds that Animal Intincts uses romance as the theme, progressive plot, and a main character who has an extraordinary personality and has her ‘animal’ instinct. The witer concludes that humans have two aspects in their life, namely love and trust, which can lead humans to the truth in their life.